2004
DOI: 10.2337/diacare.27.7.1668
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Weakness and Foot Deformities in Diabetes

Abstract: OBJECTIVE -To examine the relationships among muscle weakness, foot deformities, and peroneal and tibial nerve conduction velocity in diabetic and nondiabetic men. RESEARCH DESIGN AND METHODS-A neuropathic and foot evaluation was undertaken in 10 nondiabetic control subjects (group C) and in 36 consecutive diabetic patients attending Diabetes Centre clinics, including 10 diabetic control subjects (group D), 15 diabetic neuropathic patients (group DN), and 11 diabetic patients with a history of ulceration (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 37 publications
4
82
0
9
Order By: Relevance
“…Similar to previous research, our studies have determined a relationship between neurologic disability scores and nerve conduction values (23,24). Our study has also shown that sensory and autonomous neuropathies usually progress as the diabetes period prolongs, which is also consistent with the literature (25).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous research, our studies have determined a relationship between neurologic disability scores and nerve conduction values (23,24). Our study has also shown that sensory and autonomous neuropathies usually progress as the diabetes period prolongs, which is also consistent with the literature (25).…”
Section: Discussionsupporting
confidence: 91%
“…Van Schie et al determined decreased peroneal nerve conduction, particularly in the tibial nerve, with increased muscle weakness in groups with a history of diabetic neuropathy or diabetic foot ulcer, and described that this might be an independent risk factor for development of foot ulcer development (23). Comparison of muscle strength and ENG findings in our subjects demonstrated a decreased nerve conduction velocity and increased distal latency depending on the degree of muscle weakness and clinical severity of polyneuropathy.…”
Section: Discussionsupporting
confidence: 49%
“…Lower extremity problems represent the most common source of complications and hospitalization in the diabetic population [1] . Previous studies of persons with diabetes have identified neuropathy (loss of protective sensation), peripheral vascular disease, prior foot ulcer, or previous amputation as risk factors for developing a foot ulcer [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study, high HbA 1c , height, female sex, and cigarette smoking were independent risk factors for progression of diabetic polyneuropathy (10). Weakness evaluated by manual testing has been reported to be an independent risk factor for the development of foot ulcers (11,12), probably because muscle weakness at the ankle and knee in diabetic neuropathy leads to abnormal application of pressure at the sole of the foot during walking (2). This indicates that motor dysfunction is of importance for this severe neuropathic complication and is relevant to monitor in the clinic and in clinical trials.…”
mentioning
confidence: 99%